Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1071/wf08067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a native legume on soil N and plant response following prescribed fire in sagebrush steppe

Abstract: Abstract. Woodland expansion affects grasslands and shrublands on a global scale. Prescribed fire is a potential restoration tool, but recovery depends on nutrient availability and species responses after burning. Fire often leads to longterm losses in total nitrogen, but presence of native legumes can influence recovery through addition of fixed nitrogen. We examined the effects of prescribed fire in the central Great Basin, Nevada, USA, on density, biomass and nutrient content of a native legume, Lupinus arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 75 publications
(99 reference statements)
0
30
0
Order By: Relevance
“…The mixed-grass prairie of the Northern Great Plains developed under the influence of multiple disturbances, such as fire and grazing (e.g., Bowman et al 2009;Coppedge 1998). In native, mixed-grass prairie sites, available nitrogen is sequestered in belowground organic matter, and intense prairie fires reduced available nitrogen through volatilization and transfer of organic N from labile to recalcitrant pools (Goergen and Chambers 2009). Additionally, most native grasses and forbs exhibit high carbon : low nitrogen ratios further delaying breakdown and reducing available nitrogen for plant growth.…”
Section: Supporting Ecosystem Services Alteration Of Nutrientmentioning
confidence: 98%
“…The mixed-grass prairie of the Northern Great Plains developed under the influence of multiple disturbances, such as fire and grazing (e.g., Bowman et al 2009;Coppedge 1998). In native, mixed-grass prairie sites, available nitrogen is sequestered in belowground organic matter, and intense prairie fires reduced available nitrogen through volatilization and transfer of organic N from labile to recalcitrant pools (Goergen and Chambers 2009). Additionally, most native grasses and forbs exhibit high carbon : low nitrogen ratios further delaying breakdown and reducing available nitrogen for plant growth.…”
Section: Supporting Ecosystem Services Alteration Of Nutrientmentioning
confidence: 98%
“…Disturbance events in forests are often accompanied by large losses of N, such as the removal of tree biomass during harvesting and leaching of dissolved inorganic N due to reduced uptake by trees (Knoepp and Swank 1997, Menge et al 2009b, Boring et al 2014, McLauchlan et al 2014. This process results in soils with locally elevated N mineralization and nitrification rates (Montagnini et al 1986) and inorganic N availability (Goergen and Chambers 2009), which may facilitate the growth of neighboring nonfixers (DeBell et al 1997). This process results in soils with locally elevated N mineralization and nitrification rates (Montagnini et al 1986) and inorganic N availability (Goergen and Chambers 2009), which may facilitate the growth of neighboring nonfixers (DeBell et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fixing plants, such as Lupinus argenteus, Pursh (silvery lupine), have the potential to influence plant succession in A. t. ssp. vaseyana steppe by modifying post-fire N availability (Goergen and Chambers 2009). However, B. tectorum cover did not appear to be greater in the presence of C. velutinus, hence we concluded that the lack of perennial herbaceous vegetation on the Phase 3 sites allowed post-fire B. tectorum dominance.…”
Section: Shrub Recoverymentioning
confidence: 99%